Aula de Arte no ensino médio: o ensino de meios audiovisuais em uma perspectiva intercultural - Graciano-Dias, Jaqueline (2019)
The audiovisual sector plays a major role in relation to a contemporary society. Note that much has been discussed about of the use of these resources in the educational sphere in which are present, but most of the time as a “facilitator” and not as a valuable object of study. Thus, the research seeks to demystify the use of audiovisual means only as auxiliaries and ensure their performance so that they are able to promote meaningful learning. The TV vignette carries with it elements that when analyzed critically in the Art subject shows a cultural project of a great importance relation to a education. It’s necessary a study of the practice that seeks to promote interculturalism in the classroom, considering that television vignette is one of the student’s culture influencer and should not be ignored in their learning process, including the local culture and the teacher’s culture and creating then a new culture. The hybridization of cultures brings meaningful learning to the students without the critical sense being disregarded.